The Level of Practicing Innovative Leadership Strategies to Support Total Quality Management Requirements among Employees in Sports Activities at Iraqi Universities (Journal of the College of Basic Education, 2026)
This study aimed to identify the level of practicing innovative leadership strategies to support Total Quality Management (TQM) requirements among employees working in sports activities at Iraqi universities, as well as to examine differences in the level of such practice according to certain demographic variables, particularly gender. The study was based on the importance of innovative leadership as one of the modern administrative approaches that contribute to improving institutional performance, fostering a culture of creativity, and supporting TQM requirements in university institutions, especially in the sports activities sector, which plays an important educational and developmental role .The study adopted the descriptive–comparative method due to its suitability for the nature of the research. The research population consisted of employees working in sports activities at Iraqi universities, while the research sample included (80) male and female participants selected randomly. To collect data, the researcher used a questionnaire specifically designed to measure innovative leadership in supporting TQM requirements. The questionnaire comprised four main dimensions: innovative vision and strategic planning, encouragement of creativity and job empowerment, continuous improvement and change management, and quality-based decision-making and teamwork.The results showed that the level of practicing innovative leadership strategies to support TQM requirements among employees in sports activities at Iraqi universities was generally moderate, with variation across the different dimensions. The study recommended the adoption of specialized training and development programs targeting leaders and employees in sports activities at Iraqi universities.